Dimensi Aksiologis Pendidikan Islam - Angraini, Yunita; Maulinda, Yulis (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2023)
Axiology is a branch of philosophy that talks about or discusses orientation or value in a life. Axiology is divided into two, namely ethics and aesthetics. Ethics is divided into two, the first is descriptive ethics and the second is normative ethics, while for aesthetics, there are descriptive aesthetics and normative aesthetics. Axiology in Islamic education is still questionable. The reason is, there are still many criminals committed by islamic education output actors. So that in this article will be presented how the implications of value education in Islamic education in order to be a reference for Islamic education stakeholders in the axiological dimension. This article uses qualitative research with library research types. Speaking of axiological (value) issues in relation to Islamic education consists of two approaches, namely ethics and aesthetics which means that all processes must have value. There are two values, namely the value of ilahiyah and insaniyah. Furthermore, the implications of value education in Islamic education can be seen from the purpose (being a person who is kamil), material (incorporated islamic teaching values), methods (sourced to the Quran and hadith), evaluation (evaluating physical and spiritual dimensions), and the role of educators (a teacher must believe, be obedient, noble in character, worthy of example).